Line parameters measurements and modeling for the ν6 band of CH3F: Generation of a complete line list for atmospheric databases. (December 2016) - Jacquemart, D.; Guinet, M.
Abstract: The 8.5 µm-spectral region of methyl fluoride was studied in terms of line positions, intensities and self-broadening coefficients at room temperature. A multispectrum fitting was used to retrieve from 7 high-resolution Fourier transform spectra line parameters for 787 transitions belonging to the ν6 band between 1078 and 1240 cm −1 . The accuracy of line intensities and widths measurements were estimated to be around 5% and 5–10% respectively. J - and K -rotational dependences of the transition dipole moment squared and the self-broadening coefficients were observed and modeled from the measurements. A complete line list of almost 1500 transitions was generated for atmospheric or industrial detection of CH3 F. Comparisons with previous studies from the literature were also performed. Graphical abstract: Highlights: Fourier transform spectroscopy of the ν6 band of methyl fluoride at room temperature. Line positions, intensities and self-broadening coefficients for 787 transitions. Comparisons with measurements from literature are presented. Line list of 1499 transitions of the ν6 band has been generated.